Mobbing w środowisku pracy. Rys teoretyczny = Workplace mobbing - theoretical perspective - Góralewska-Słońska, Anna Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article presents major definitions of mobbing, mobbing activities and mobbing processes. It describes mobbing determinants in four aspects: (1) personality traits of the mobber, (2) personality and social factors determining a mobbing victim, (3) organizational factors and (4) socioeconomic factors. The article also discusses the consequences of mobbing for the individual, organization and society. Mobbing is presented as a major organizational pathology.
Keywords: definicja mobbingu; fazy i działania mobbingowe; czynniki determinujące mobbing; konsekwencje mobbingu; definition of mobbing; mobbing phases and activities; factors determining mobbing; consequences of mobbing